THE ROUGH SET METHOD IN MEASURING EMPLOYEE PERFORMANCE - M Afuan (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2021)
Performance has a very important role because performance is a form of the end result of an employee's process in completing his duties. Employees who can complete their duties properly and correctly will have high performance. Therefore Punctuality, Technical Knowledge Regarding Work, Communication between Employees, and the Ability to Manage Work are believed to be able to influence the performance of an employee. To further accelerate the measurement of performance, a method is needed to measure it. The thought set method is a solution for measuring an employee's performance in several steps, namely: Decision System, Equivalence Class, Discernibilty Matric, Reduction, and Rules. This study measures the performance of employees using the Rough Set method on employees of the Qiana Padang Wholesale Store with a sample of 10 employees, so the results of this study are based on 10 samples of employees of the Qiana Padang Store which were carried out by testing using the Rough Set application. The employees of Toko Qiana Padang showed good results as many as 4 employees and there were as many as 6 employees who had excellent performance